Emotional–behavioral resilience among children of first-time mothers with and without depression across the early childhood period. (March 2018) - Giallo, Rebecca; Gartland, Deirdre; Woolhouse, Hannah; Mensah, Fiona; Westrupp, Elizabeth; Nicholson, Jan; Brown, Stephanie
The deleterious effects of maternal depression on child emotional and behavioral development are well documented, yet many children exposed to maternal depression experience positive outcomes. The aim of this study was to identify psychosocial factors associated with the emotional–behavioral resilience of four-year-old children of first-time mothers experiencing depressive symptoms across the early childhood period. Data were from 1085 mother–child dyads in the Maternal Health Study collected prospectively at five time-points from pregnancy to child age four. Longitudinal trajectories of maternal depressive symptoms were identified, and children were regarded as resilient or competent if they scored in the normal range on the Total Difficulties subscale of the Strengths and Difficulties Questionnaire. We found that 22% of women had a pattern of moderate to high depressive symptoms, and within this group 78% of their children were identified as resilient. Maternal tertiary education and maternal involvement in home learning activities were unique predictors of children's resilience. Higher maternal age at the time of pregnancy and financial security were factors associated with positive outcomes for all children. The findings highlight the importance of policy and intervention efforts to strengthen the quality of maternal–child interactions and the home learning environment to promote the emotional and behavioral functioning of children whose mothers are experiencing mental health difficulties in the early years of parenting.